RANCANG BANGUN AUTOMATIC PRESS TOOL UNTUK BLANKING CETAKAN KUE - Muhammad Arsyad Suyuti; Ahmad Zubair Sultan; Muhammad Ardiansyah; Rezky Aryadi Mihdar; Gede Yudi Swastika (Politeknik Negeri Ujung Pandang, 2019)
Press tools can produce products in bulk with uniform quality and short time. The automation system applied to this press tool is a system to help channel metal plates to the press tool automatically called a feeder so that it can be called an automatic press tool. The technique that will be applied in this press tool is blanking technique. Blanking is a product of forming results that is used and is produced from one single cutting process with all forms of contour being cut in full, or the result of gradual cutting with the press tool. This research aims to design and prototype an automatic press tool to produce cake mold blanking using a pneumatic system that can work more effectively and efficiently. The research method was carried out in several stages, namely the design phase, the manufacturing stage, the assembly stage and the data analysis. The results obtained from this study produce automatic press tool blanking cake molds with a pneumatic system that is given a maximum compressive strength of 8 bars and a pressure force of 6280 N. This tool is able to produce aluminum blanking results on average of 17 to 18 pieces per minute without requiring a load high operator work.